Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1136/jcp.46.8.754
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Helicobacter pylori colonisation and associated gastric inflammatory changes: difference between patients with duodenal and gastric ulcers.

Abstract: Aims-To determine the gastric distribution of Helicobacter pylon in patients with duodenal and gastric ulcers; and to examine the mucosal inflammatory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 11 publications
5
25
0
1
Order By: Relevance
“…The degree of neutrophil in®ltra-tion in the body in duodenal ulcer patients was signi®cantly smaller in comparison with those with chronic gastritis in spite of the fact that there was no difference in the density of H. pylori and mucosal IL-8 content between the two groups. In general, duodenal ulcer patients are known to have high acid secretion, 18,19 and fewer DU patients have been reported to have histological gastritis in the body in comparison with those who do not have ulcer or those who have gastric ulcer. 20,21 This was assumed by Solcia et al 20 to be attributable to the possibility of attenuation of the damage caused by H. pylori on the mucosa through the transformation from ammonia to ammonium chloride by acid.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of neutrophil in®ltra-tion in the body in duodenal ulcer patients was signi®cantly smaller in comparison with those with chronic gastritis in spite of the fact that there was no difference in the density of H. pylori and mucosal IL-8 content between the two groups. In general, duodenal ulcer patients are known to have high acid secretion, 18,19 and fewer DU patients have been reported to have histological gastritis in the body in comparison with those who do not have ulcer or those who have gastric ulcer. 20,21 This was assumed by Solcia et al 20 to be attributable to the possibility of attenuation of the damage caused by H. pylori on the mucosa through the transformation from ammonia to ammonium chloride by acid.…”
Section: Discussionmentioning
confidence: 99%
“…Previous South African studies 10,13,17 had equally incriminated this organism in cases of duodenal and gastric ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Although studies have reported the prevalence of the organism in the country, most adopted a sero-prevalence approach, which does not provide more information other than the presence of antibodies, which are poor markers of active infection. In Cape Town, a prevalence of 63% of the pathogen in NUD patients based on histology reports was documented, 13 and a prevalence of 81% in NUD patients based on serology testing. 17 Published data on the prevalence of the organism in dyspeptic patients in the Eastern Cape province, which is predominantly rural with poor sanitation and household hygiene (factors that favour the spread of H. pylori), are lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11]. These alterations in acid secretion depend on the degree and distribution of gastritis caused by the infection [29,30]. In subjects with an antral predominant gastritis, without atrophy, acid secretion is normal or increased.…”
Section: H Pylori Infection and Gastric Acid Perturbationmentioning
confidence: 99%